Implementation of robotic devices in nursing care. Barriers and facilitators: an integrative review. Issue 9 (21st September 2020) - Servaty, Ricarda; Kersten, Annalena; Brukamp, Kirsten; Möhler, Ralph; Mueller, Martin
Abstract : Background: Robots in healthcare are gaining increasing attention; however, their implementation is challenging due to the complexity of both interventions themselves and the contexts in which they are implemented. The objective of this integrative review is to identify barriers to and facilitators of the implementation of robotic systems in nursing. Methods: Articles published from 2002 to 2019 reporting on projects to implement robotic devices in nursing care were searched on Medline (via PubMed), CINAHL and databases on funded research projects (Community Research and Development Information Services and Technische Informationsbibliothek) and in journals for robotic research in November 2017 and July 2019 for an update. No restrictions regarding study designs were imposed. All included articles underwent quality assessments with design-specific critical appraisal tools. Barriers to and facilitators of implementation were classified using the Context and Implementation of Complex Interventions framework. Results: After removing all duplicates, the search revealed 11 204 studies, of which 17 met the inclusion criteria and were included in the synthesis. The majority of the studies dealt with the implementation of robots designed to support individuals, either living at home or in nursing homes (n=11). The studies were conducted in Europe, the USA and New Zealand and were carried out in nursing homes, individual living environments, hospital units and laboratories. The quality of reporting and quality of evidence were low in most studies. The most frequently reported barriers were in socioeconomic and ethical domains and were within the implementation outcomes domain. The most frequently reported facilitators were related to the sociocultural context, implementation process and implementation strategies. Discussion: This review identified barriers to and facilitators of the implementation of robotic devices in nursing within different dimensions. The results serve as a basis for the development of suitable implementation strategies to reduce potential barriers and promote the integration of elements to facilitate implementation. PROSPERO registration number: CRD42018073486.